Avaliação da expressão da granzima b e sua relação com o prognóstico do carcinoma espinocelular de boca - COSTA, Nádia do Lago (2010)
The cytotoxic T lymphocytes (CTL) and natural killer (NK) cells are more effective in fighting cancer because these cells recognize tumor cells and release cytotoxic granules rich in perforin and granzyme B (GB). The perforin form pores in tumor cells allowing the influx of GB. When inside the cell, the GB promotes tumor cell death through apoptosis. In this context, high expression of GB into the microenvironment of different types of cancers has been considered a key event for effective antitumor immunity. Therefore, the objective of this study was to identify and quantify GB+ cells, peri- and intratumoral, and its relationship with clinical prognostic parameters (size of the primary lesion, location, metastasis and survival) and microscopic (microscopic grading and cell proliferation index and apoptosis of neoplastic cells) of squamous cell carcinoma (SCC) of the oral cavity. GB+ cells were identified by the technique of immunohistochemistry, a method of polymer, in 20 samples from patients with SCC of the oral cavity that had metastasized to cervical lymph nodes and in 35 samples from patients with SCC of the oral cavity without metastasis to cervical lymph nodes. Our results showed that the density of peritumoral GB+ cells was significantly higher in the non-metastatic SCC when compared with metastatic group (p=0.03). In addition, patients with high expression of peritumoral GB had a longer survival than those with low expression of this protease (Kaplan Meier, Log Rank p=0.02). We showed also that patients with high density of peritumoral GB+ cells showed a low percentage of neoplastic cells bcl2+ (antiapoptotic protein) (P=0.004) and high density of neoplastic cells Bax+ (apoptotic protein) (p=0.031) when compared to the group of low density of peritumoral GB+ cells. In agreement with these data, patients who had a high density of peritumoral GB+ cells showed high expression of Annexin V by neoplastic cells. Additionally, the density of GB+ cells intratumoral and peritumoral was significantly higher in the T1 and T2 (39.44±7.21 and 14.61±3.60, respectively) when compared to T3 and T4 (31.03±3.76 and 11.90±1.88, respectively), however these results were not statistically significant (p>0.05). The association between the density of cells GB+ and other characteristics of SCC of the oral cavity, such as location, tumor proliferation and tumor grading was not observed. Our findings suggest that the increased of expression of GB in tumor microenvironment of SCC of the oral cavity may have beneficial effect against neoplastics cells, contributing to apoptosis of these cells, lower lymph node involvement and increased survival time of patients.